The relationship between health literacy, digital diet literacy, and health behaviors: A cross-sectional study - Soylar, Pinar; Demirel, Emre (My University, 2025)
Our objective was to investigate the association between health literacy (HL), digital diet health literacy (DDHL), and healthy behaviors among adults in Türkiye. This descriptive study investigates the association between HL, DDHL, and healthy behaviors in Türkiye. Participants (n=464) were selected from family health centers and filled out a structured questionnaire addressing health literacy, digital diet health literacy, and health behaviors. Data from 36.42±11.24-year-old participants (72% female) revealed that 83% of participants had no chronic illnesses, but 68.8% lacked regular physical activity. The study found a notable moderate positive association between HL and DDHL (r=0.420, p<0.001). Health literacy was a strong predictor of DDHL, and age was found to negatively affect DDHL. Older participants exhibited lower DDHL scores, while health behaviors like vitamin supplementation positively influenced DDHL. Alcohol consumption negatively impacted DDHL. The study confirms the significant relationship between HL and DDHL, with health literacy positively influencing digital literacy skills, especially regarding nutrition. Public health interventions should focus on enhancing these skills, particularly among older adults and individuals with low literacy levels
Keywords: Türkiye; adults; Health literacy; health behaviors; digital diet health literacy